Composite solid electrolyte and all-solid-state battery containing the same
Patent Information
- Application Number
- JP2024548762
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-03-02
- Filing Date
- 2023-03-02
- Publication Date
- 2025-03-13
- Estimated Expiration
- 2043-03-02
AI Technical Summary
【0021】 本発明に係る複合固体電解質は、硫化物系固体電解質粒子上に大気安定性および耐薬品性に優れた高分子コーティング層が形成されており、複合固体電解質自体の大気安定性に優れるだけでなく、電池の製造時に湿式(wet)工程で耐薬品性が改善されることができる。
Smart Images

Figure 2025506724000001 
Figure 2025506724000002 
Figure 2025506724000003
Abstract
Description
[Technical field]
[0001] This application claims the benefit of priority based on Korean Patent Application No. 10-2022-0026992, filed on March 2, 2022, the entire contents of which are incorporated herein by reference.
[0002] The present invention relates to a sulfide-based composite solid electrolyte having improved atmospheric stability and chemical resistance, and an all-solid-state battery including the same. [Background technology]
[0003] As technological development and demand for electric vehicles as well as mobile devices increases, the demand for secondary batteries as energy sources is rapidly increasing. In general, secondary batteries are composed of a positive electrode, a negative electrode, an electrolyte located therebetween, and a separator. Currently, the most widely used secondary battery is the lithium secondary battery, which generally uses a liquid electrolyte as the electrolyte. However, liquid electrolytes are vulnerable to heat and impact and are highly flammable, and therefore lithium secondary batteries have the problem of being damaged by external impact or exploding due to an increase in temperature.
[0004] In order to solve the above-mentioned problems, all-solid-state batteries are batteries in which the liquid electrolyte that fills the gap between the positive and negative electrodes of conventional lithium secondary batteries is replaced with a solid electrolyte. They are safe, have no risk of explosion, and have a higher energy density than conventional batteries, and are attracting attention as next-generation batteries. The solid electrolyte used in all-solid-state batteries is a solid-state material that can conduct lithium ions in the battery, and has a high ionic conductivity at the same level as the electrolyte used in current lithium secondary batteries. Core materials that make up solid electrolytes include polymers, sulfides, and oxides, and among them, sulfide-based solid electrolytes, which have high ductility and high ionic conductivity, are evaluated to be suitable for manufacturing large-capacity batteries.
[0005] However, sulfide-based solid electrolytes are highly reactive to moisture, and react not only with moisture in the air but also with moisture under low humidity conditions, generating the harmful gas hydrogen sulfide (H2S). This not only poses a risk to the safety of workers, but also leads to problems such as deterioration of the performance of the sulfide-based solid electrolyte itself. Therefore, there is a need to develop a sulfide-based solid electrolyte that has excellent atmospheric stability and chemical resistance. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] JP 2020-135947 A [Patent Document 2] China Patent Publication Publication CN112701345A Summary of the Invention [Problem to be solved by the invention]
[0007] It is an object of the present invention to provide a composite solid electrolyte having improved atmospheric stability and chemical resistance. However, the problems that the present invention is intended to solve are not limited to those mentioned above, and other problems not mentioned will be clearly understood by those skilled in the art from the following description. [Means for solving the problem]
[0008] In order to solve the above problems, the present invention provides a composite solid electrolyte and an all-solid-state battery. (1) The present invention provides a battery comprising sulfide-based solid electrolyte particles and a polymer coating layer formed on the sulfide-based solid electrolyte particles, The polymer coating layer includes a polymer having a weight average molecular weight (Mw) of 5,000 g / mol to 300,000 g / mol and a contact angle with water of 100° or more at 25° C., The polymer of the polymer coating layer is a copolymer of a hydrophobic acrylate monomer and an acrylate monomer forming a polymer backbone, The hydrophobic acrylate monomer contains an F element or an Si element, or contains a hydrocarbon having 10 or more carbon atoms, The acrylate monomer forming the polymer backbone provides a composite solid electrolyte containing a hydrocarbon having 9 or less carbon atoms.
[0009] (2) In the present invention, there is provided the composite solid electrolyte according to (1) above, wherein the sulfide-based solid electrolyte has a silver germanite crystal structure.
[0010] (3) In the present invention, there is provided the composite solid electrolyte according to (1) or (2) above, wherein the hydrophobic acrylate monomer is at least one selected from the group consisting of polydimethylsiloxane-based (meth)acrylate, N-octadecyl (meth)acrylate, stearyl (meth)acrylate, and perfluorohexylethyl (meth)acrylate.
[0011] (4) In the present invention, there is provided the composite solid electrolyte according to any one of (1) to (3), wherein the acrylate monomer forming the polymer skeleton is at least one selected from cyclohexyl (meth)acrylate, methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, iso-propyl (meth)acrylate, n-butyl (meth)acrylate, iso-butyl (meth)acrylate, tert-butyl (meth)acrylate, n-pentyl (meth)acrylate, and iso-pentyl (meth)acrylate.
[0012] (5) In the present invention, there is provided the composite solid electrolyte according to any one of (1) to (4), wherein the polymer of the polymer coating layer contains a repeating unit represented by the following chemical formula 1 and a repeating unit represented by the following chemical formula 2:
[0013] [ka]
[0014] In the above Chemical Formula 1, R1 is hydrogen; or C1-C 10 is an alkyl group of the formula R2 is a C4-C containing cyclic hydrocarbon 10 is an alkyl group of the formula
[0015] [ka]
[0016] In the above Chemical Formula 2, R3 to R8 are each independently hydrogen; or C1-C 10 is an alkyl group of the formula R9 is a direct bond; C1-C 10 Alkylene group; C2-C 10 Alkenylene group; C1-C 10 Oxyalkylene group; C6-C 30 or an arylene group of C6-C 30 is an oxyarylene group of the formula n is an integer of 1 or greater.
[0017] (6) The present invention provides the composite solid electrolyte according to any one of (1) to (5) above, in which the polymer coating layer is contained in an amount of 0.1 to 10 parts by weight per 100 parts by weight of the sulfide-based solid electrolyte particles.
[0018] (7) The present invention provides the composite solid electrolyte according to any one of (1) to (6) above, which has an ion conductivity of 0.001 mS / cm or more.
[0019] (8) The present invention relates to a method for producing a composite solid electrolyte, comprising: exposing the composite solid electrolyte to an inert atmosphere at a temperature of 25° C. and a relative humidity of 0.5% to 0.6%; and determining whether the rate of hydrogen sulfide (HS) generation is 10 cm per 1 g of the composite solid electrolyte after 1 hour of exposure. 3 / h or less.
[0020] (9) The present invention provides an all-solid-state battery including the composite solid electrolyte according to any one of (1) to (8) above. Effect of the Invention
[0021] In the composite solid electrolyte according to the present invention, a polymer coating layer having excellent atmospheric stability and chemical resistance is formed on sulfide-based solid electrolyte particles, and thus the composite solid electrolyte itself has excellent atmospheric stability, and the chemical resistance can be improved in a wet process during battery manufacturing. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0022] The present invention will now be described in more detail to aid in understanding the invention. The terms and words used in this specification should not be interpreted in a limited manner to their ordinary or dictionary meanings, but should be interpreted in a manner that is consistent with the technical idea of the present invention, based on the principle that the inventors can appropriately define the concepts of terms in order to best describe their invention.
[0023] The terms used in this specification are merely used to describe exemplary embodiments and are not intended to limit the present invention. The singular expressions include the plural expressions unless otherwise clearly indicated in the context.
[0024] It should be understood that, as used herein, terms such as "comprises," "comprising," or "having" are intended to specify the presence of embodied features, numbers, steps, components, or combinations thereof, but do not preclude the presence or additional possibility of one or more other features, numbers, steps, components, or combinations thereof.
[0025] Composite solid electrolyte The composite solid electrolyte according to the present invention includes sulfide-based solid electrolyte particles and a polymer coating layer formed on the sulfide-based solid electrolyte particles, the polymer coating layer including a polymer having a weight average molecular weight (Mw) of 5,000 g / mol to 300,000 g / mol and a contact angle with water of 100° or more at 25° C. The polymer of the polymer coating layer is a copolymer of a hydrophobic acrylate monomer and an acrylate monomer forming the backbone of the polymer. The hydrophobic acrylate monomer contains an F element or an Si element or contains a hydrocarbon having 10 or more carbon atoms, and the acrylate monomer forming the backbone of the polymer contains a hydrocarbon having 9 or less carbon atoms.
[0026] The present inventors have found that in the case of the composite solid electrolyte according to the present invention, a polymer coating layer having excellent atmospheric stability (excellent moisture and oxygen barrier performance) is formed on the sulfide-based solid electrolyte particles, and thus the composite solid electrolyte itself has excellent atmospheric stability, and also has improved chemical resistance in dry and wet processes during battery manufacturing, thereby completing the present invention.
[0027] In the composite solid electrolyte according to the present invention, the polymer coating layer contains a polymer having a weight-average molecular weight (Mw) of 5,000 g / mol to 300,000 g / mol and a contact angle with water of 100° or more at 25° C., and can suppress decomposition and deterioration of the sulfide-based solid electrolyte particles when exposed to moisture or oxygen. As a result, generation of hydrogen sulfide, which is a toxic gas, can be suppressed, and a decrease in the ionic conductivity of the composite solid electrolyte can be prevented.
[0028] The polymer of the polymer coating layer is generally a polymer having high compatibility with the binder polymer of the battery, and is a polymer of an acrylate monomer. The polymer of the polymer coating layer is a copolymer of two or more kinds of acrylate monomers, and specifically, the polymer of the polymer coating layer is a copolymer of a hydrophobic acrylate monomer and an acrylate monomer forming a polymer backbone.
[0029] More specifically, the polymer of the polymer coating layer may be a copolymer obtained by polymerizing a hydrophobic acrylate monomer and an acrylate monomer forming the polymer backbone in a weight ratio of 1:99 to 10:90.
[0030] According to the present invention, the sulfide-based solid electrolyte may have a silver germanite crystal structure in terms of high ionic conductivity and low reactivity with a lithium negative electrode. The sulfide-based solid electrolyte may be a sulfide-based solid electrolyte containing Li, P, and S. For example, the sulfide-based solid electrolyte may be a sulfide-based solid electrolyte containing Li, P, and S. 7-x P.S. 6-x A x (wherein A may be Cl, Br, I, Sn, or a combination thereof, and x is 0≦x≦2).
[0031] The polymer coating layer includes a polymer having a weight average molecular weight (Mw) of 5,000 g / mol to 300,000 g / mol. The weight average molecular weight (Mw) of the polymer may be specifically 5,000 g / mol to 200,000 g / mol, more specifically 10,000 g / mol to 100,000 g / mol. On the other hand, if the weight average molecular weight (Mw) of the polymer is less than 5,000 g / mol, the amount of remaining monomers that do not participate in the polymer polymerization reaction is high, and the moisture blocking effect is insufficient. If it exceeds 300,000 g / mol, the contact between the sulfide-based solid electrolyte particles may be reduced, and the ion conductivity may be reduced.
[0032] The polymer of the polymer coating layer may have a contact angle to water of 100° or more, specifically 100° to 170°, more specifically 110° to 170° at 25° C. In this case, the water repellency of the composite solid electrolyte can be excellent.
[0033] The hydrophobic acrylate monomer may contain an F element or an Si element capable of imparting water repellency, or may contain a hydrocarbon having 10 or more carbon atoms. The hydrophobic acrylate monomer may be a fluorine-containing (meth)acrylate monomer, a silicon-containing (meth)acrylate monomer, or a C 10 -C 20 In this case, the (meth)acrylate refers to a methacrylate or an acrylate. 10 -C 20 The hydrocarbon may be a linear or branched chain hydrocarbon; a cyclic hydrocarbon; or a simultaneous linear or branched chain and ring hydrocarbon.
[0034] Specifically, the hydrophobic acrylate monomer may be one or more selected from polydimethylsiloxane-based (meth)acrylate, N-octadecyl (meth)acrylate, stearyl (meth)acrylate, and perfluorohexylethyl (meth)acrylate. More specifically, the acrylate monomer may be polydimethylsiloxane-based (meth)acrylate, such as α-butyl-ω-(3-methacryloxypropyl)polydimethylsiloxane.
[0035] The acrylate monomer forming the backbone of the polymer is a monomer forming the main chain of the polymer and may contain a hydrocarbon having 9 or less carbon atoms. The acrylate monomer forming the backbone of the polymer may be a C1-C9 hydrocarbon-containing (meth)acrylate monomer. In this case, (meth)acrylate means methacrylate or acrylate. The C1-C9 hydrocarbon may be a linear or branched chain hydrocarbon; a cyclic hydrocarbon; or a hydrocarbon having both a linear or branched chain and a ring.
[0036] Specifically, the acrylate monomer forming the backbone of the polymer may be one or more selected from cyclohexyl (meth)acrylate, methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, iso-propyl (meth)acrylate, n-butyl (meth)acrylate, iso-butyl (meth)acrylate, tert-butyl (meth)acrylate, n-pentyl (meth)acrylate, and iso-pentyl (meth)acrylate.
[0037] The polymer of the polymer coating layer may be, for example, a copolymer of polydimethylsiloxane-based (meth)acrylate and cyclohexyl (meth)acrylate, specifically, a copolymer obtained by polymerizing polydimethylsiloxane-based (meth)acrylate and cyclohexyl (meth)acrylate in a weight ratio of 1:99 to 10:90.
[0038] According to the present invention, the polymer of the polymer coating layer may include a repeating unit represented by the following Chemical Formula 1 and a repeating unit represented by the following Chemical Formula 2:
[0039] [ka]
[0040] In the above Chemical Formula 1, R1 is hydrogen; or C1-C 10 is an alkyl group of the formula R2 is a C4-C containing cyclic hydrocarbon 10 is an alkyl group of the formula
[0041] [ka]
[0042] In the above Chemical Formula 2, R3 to R8 are each independently hydrogen; or C1-C 10 is an alkyl group of the formula R9 is a direct bond; C1-C10 Alkylene group; C2-C 10 Alkenylene group; C1-C 10 Oxyalkylene group; C6-C 30 or an arylene group of C6-C 30 is an oxyarylene group of the formula n is an integer of 1 or greater. In the repeating units represented by Chemical Formula 1 and Chemical Formula 2, * represents a portion that bonds to another repeating unit.
[0043] The polymer may contain repeating units represented by Chemical Formula 1 and repeating units represented by Chemical Formula 2 in a ratio of 1:99 to 10:90 in order to improve the moisture barrier effect and minimize the decrease in ion conductivity.
[0044] According to the present invention, the polymer coating layer may be included in an amount of 0.1 to 10 parts by weight, specifically 0.1 to 7 parts by weight, more specifically 0.5 to 5 parts by weight, based on 100 parts by weight of the sulfide-based solid electrolyte particles, whereby the moisture blocking effect is improved and the decrease in ion conductivity can be minimized.
[0045] According to the present invention, the composite solid electrolyte may have an ionic conductivity of 0.001 mS / cm or more, specifically 0.001 mS / cm to 20 mS / cm, more specifically 0.01 mS / cm to 10 mS / cm, or 0.01 mS / cm to 5 mS / cm. The higher the ionic conductivity of the electrolyte, the better. However, when the polymer coating layer is formed so that the ionic conductivity satisfies the above range as in the present invention, the moisture stability effect can be improved. The ionic conductivity can be measured in a dry room at a temperature of 22°C and a relative humidity of 0.7%.
[0046] According to the present invention, when the composite solid electrolyte is exposed to an inert atmosphere, a temperature of 25° C., and a relative humidity of 0.5% to 0.6%, the rate of hydrogen sulfide (H2S) generation at the time of 1 hour after exposure is 10 cm3 per 1 g of the composite solid electrolyte. 3 / h or less. That is, the composite solid electrolyte according to the present invention has excellent water stability, has a low rate of decrease in ionic conductivity even after exposure to water, and generates a small amount and a slow rate of hydrogen sulfide, which is a toxic gas, to ensure process safety.
[0047] The composite solid electrolyte has a hydrogen sulfide (H2S) generation rate of 10 cm3 per 1 g of the composite solid electrolyte in the first hour when the composite solid electrolyte is exposed to an inert atmosphere at a temperature of 25°C and a relative humidity of 0.5% to 0.6%. 3 It may be the following.
[0048] The composite solid electrolyte according to the present invention can be produced by coating sulfide-based solid electrolyte particles with a polymer composition containing a polymer having a weight average molecular weight (Mw) of 5,000 g / mol to 300,000 g / mol.
[0049] The sulfide-based solid electrolyte particles can be synthesized, for example, by mechanical milling. Specifically, three precursors, Li2S, P2S5, and LiCl, are weighed according to stoichiometry and then mixed by ball milling. The resulting mixed precursor is heat-treated to crystallize, and then pulverized again by ball milling. The mixing, heat treatment, and pulverization processes are carried out in an inert gas atmosphere.
[0050] The polymer having a weight average molecular weight (Mw) of 5,000 g / mol to 300,000 g / mol can be produced by polymerizing the above-mentioned acrylate monomers by a method such as suspension polymerization, solution polymerization, bulk polymerization, etc. For example, the above-mentioned acrylate monomers, optionally a chain transfer agent, a dispersant, a thermal initiator, etc., can be dispersed in a solvent, and then the mixture is mixed with a stirrer to carry out suspension polymerization to produce the polymer.
[0051] The polymer composition may be prepared by dissolving or dispersing the polymer having a weight average molecular weight (Mw) of 5,000 g / mol to 300,000 g / mol in a solvent such as toluene, xylene, etc. In this case, the weight ratio of the polymer having a weight average molecular weight (Mw) of 5,000 g / mol to 300,000 g / mol to the solvent such as toluene, xylene, etc. may be 1:2 to 2:1.
[0052] Finally, the coating may be performed by mixing and stirring the polymer composition and the sulfide-based solid electrolyte, followed by drying, or by spraying the polymer composition onto the sulfide-based solid electrolyte, followed by drying, but is not limited thereto and may be performed by a method known in the art.
[0053] all solid state battery The present invention provides an all-solid-state battery comprising the composite solid electrolyte. Specifically, the all-solid-state battery includes a positive electrode including a positive electrode active material, a negative electrode including a negative electrode active material, and a solid electrolyte layer including the composite solid electrolyte according to the present invention disposed between the positive electrode and the negative electrode.
[0054] The all-solid-state battery according to the present invention is less susceptible to a decrease in ion conductivity due to moisture, and can have excellent initial efficiency, life characteristics, and output characteristics. In this case, the all-solid-state battery of the present invention can be manufactured by a conventional method well known in the art, for example, by stacking and pressurizing the positive electrode and the negative electrode so that a solid electrolyte layer is present between them.
[0055] (1) Positive electrode The positive electrode may be prepared by coating a positive electrode current collector with a positive electrode slurry including a positive electrode active material, a binder, a conductive material, and a solvent.
[0056] The positive electrode current collector is not particularly limited as long as it does not cause a chemical change in the battery and has conductivity. For example, stainless steel, aluminum, nickel, titanium, fired carbon, or a material obtained by surface-treating the surface of aluminum or stainless steel with carbon, nickel, titanium, silver, etc. may be used. Further, fine irregularities may be formed on the surface to strengthen the binding force of the positive electrode active material, and it may be used in various forms such as a film, sheet, foil, net, porous body, foam, non-woven fabric body, etc.
[0057] The positive electrode active material is a compound capable of reversible intercalation and deintercalation of lithium. Specifically, it may contain a lithium metal oxide containing one or more metals such as cobalt, manganese, nickel, or aluminum and lithium. More specifically, the lithium metal oxide is a lithium-manganese-based oxide (e.g., LiMnO2, LiMn2O4, etc.), a lithium-cobalt-based oxide (e.g., LiCoO2, etc.), a lithium-nickel-based oxide (e.g., LiNiO2, etc.), a lithium-nickel-manganese-based oxide (e.g., LiNi 1-Y Mn Y O2 (where 0 < Y < 1), LiMn 2-z Ni z O4 (where 0 < Z < 2), etc.), a lithium-nickel-cobalt-based oxide (e.g., LiNi 1-Y1 Co Y1 O2 (where 0 < Y1 < 1), etc.), a lithium-manganese-cobalt-based oxide (e.g., LiCo 1-Y2 Mn Y2 O2 (where 0 < Y2 < 1), LiMn 2-z1 Co z1 O4 (where 0 < Z1 < 2), etc.), a lithium-nickel-manganese-cobalt-based oxide (e.g., Li(Ni p Co q Mn r1 )O2 (where 0 < p < 1, 0 < q < 1, 0 < r1 < 1, p + q + r1 = 1), or Li(Ni p1 Co q1 Mn r2)O4 (where 0 < p1 < 2, 0 < q1 < 2, 0 < r2 < 2, and p1 + q1 + r2 = 2), etc.), or lithium-nickel-cobalt-transition metal (M) oxides (e.g., Li(Ni p2 Co q2 Mn r3 M S2 )O2 (where M is selected from the group consisting of Al, Fe, V, Cr, Ti, Ta, Mg, and Mo, and p2, q2, r3, and s2 are the atomic fractions of the respective independent elements, with 0 < p2 < 1, 0 < q2 < 1, 0 < r3 < 1, 0 < s2 < 1, and p2 + q2 + r3 + s2 = 1), etc.), and any one or more of these compounds may be included.
[0058] Among them, in terms of improving the capacity characteristics and safety of the battery, the lithium metal oxide is LiCoO2, LiMnO2, LiNiO2, lithium nickel manganese cobalt oxide (e.g., Li(Ni 1 / 3 Mn 1 / 3 Co 1 / 3 )O2, Li(Ni 0.6 Mn 0.2 Co 0.2 )O2, Li(Ni 0.5 Mn 0.3 Co 0.2 )O2, Li(Ni 0.7 Mn 0.15 Co 0.15 )O2, and Li(Ni 0.8 Mn 0.1 Co 0.1 )O2, etc.), or lithium nickel cobalt aluminum oxide (e.g., Li(Ni 0.8 Co 0.15 Al 0.05 )O2, etc.), and considering the significance of the improvement effect according to the control of the types and content ratios of the constituent elements forming the lithium composite metal oxide, the lithium composite metal oxide is Li(Ni 0.6 Mn 0.2 Co 0.2 )O2, Li(Ni 0.5 Mn 0.3 Co 0.2 )O2, Li(Ni 0.7 Mn 0.15 Co0.15 )O2, and Li(Ni 0.8 Mn 0.1 Co 0.1 )O2, etc., and any one or a mixture of two or more of these may be used.
[0059] The positive electrode active material may be contained in an amount of 60% to 99% by weight, preferably 70% to 99% by weight, and more preferably 80% to 98% by weight, based on the total weight of solids in the positive electrode slurry excluding the solvent.
[0060] The binder is a component that aids in bonding between the conductive material, the active material, and the current collector. Examples of such binders include polyvinylidene fluoride, polyvinyl alcohol, carboxymethyl cellulose, starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene monomer, sulfonated ethylene-propylene-diene monomer, styrene-butadiene rubber, fluororubber, and various copolymers thereof.
[0061] Generally, the binder may be contained in an amount of 1 wt % to 20 wt %, preferably 1 wt % to 15 wt %, and more preferably 1 wt % to 10 wt %, based on the total weight of solids in the positive electrode slurry excluding the solvent.
[0062] The conductive material is a component for further improving the conductivity of the positive electrode active material. The conductive material is not particularly limited as long as it does not cause a chemical change in the battery and has conductivity, and examples of the conductive material that may be used include graphite; carbon-based substances such as carbon black, acetylene black, ketjen black, channel black, furnace black, lamp black, and thermal black; conductive fibers such as carbon fibers and metal fibers; metal powders such as carbon fluoride, aluminum, and nickel powder; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; and conductive materials such as polyphenylene derivatives.
[0063] Generally, the conductive material may be contained in an amount of 1 wt % to 20 wt %, preferably 1 wt % to 15 wt %, and more preferably 1 wt % to 10 wt %, based on the total weight of solids excluding the solvent in the positive electrode slurry.
[0064] The solvent may contain an organic solvent such as NMP (N-methyl-2-pyrrolidone), and may be used in an amount that provides a preferred viscosity when the positive electrode active material, and optionally a binder and a conductive material, etc. are contained. For example, the solvent may be contained so that the concentration of the solid content including the positive electrode active material, and optionally a binder and a conductive material, is 50% by weight to 95% by weight, preferably 70% by weight to 95% by weight, and more preferably 70% by weight to 90% by weight.
[0065] (2) Negative electrode The negative electrode may be prepared, for example, by coating a negative electrode current collector with a negative electrode slurry including a negative electrode active material, a binder, a conductive material, and a solvent, or a graphite electrode made of carbon (C) or a metal itself may be used as the negative electrode.
[0066] For example, when the negative electrode is manufactured by coating the negative electrode slurry on the negative electrode current collector, the negative electrode current collector generally has a thickness of 3 to 500 μm. Such a negative electrode current collector is not particularly limited as long as it does not cause a chemical change in the battery and has high conductivity, and for example, copper, stainless steel, aluminum, nickel, titanium, baked carbon, copper or stainless steel surface-treated with carbon, nickel, titanium, silver, etc., aluminum-cadmium alloy, etc. may be used. In addition, like the positive electrode current collector, fine irregularities may be formed on the surface to strengthen the binding force of the negative electrode active material, and it may be used in various forms such as a film, sheet, foil, net, porous body, foam, nonwoven fabric, etc.
[0067] The negative electrode active material may be natural graphite, artificial graphite, carbonaceous material, lithium-containing titanium oxide (LTO), Si, SiO x, Sn, Li, Zn, Mg, Cd, Ce, Ni, or Fe; alloys composed of the metals (Me); oxides of the metals (Me) (MeO x ); and a composite of the metal (Me) and carbon. Specific examples of the negative electrode active material include silicon (Si), silicon oxide (SiO x ), or a silicon-based negative electrode active material including a silicon alloy, etc., may be used. In this case, a thin and stable SEI layer including siloxane bonds is formed, which can further improve the high temperature stability and life characteristics of the battery.
[0068] The negative electrode active material may be contained in an amount of 60% to 99% by weight, preferably 70% to 99% by weight, and more preferably 80% to 98% by weight, based on the total weight of solids in the negative electrode slurry excluding the solvent.
[0069] The binder is a component that aids in bonding between the conductive material, the active material, and the current collector. Examples of such binders include polyvinylidene fluoride, polyvinyl alcohol, carboxymethyl cellulose, starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene monomer, sulfonated ethylene-propylene-diene monomer, styrene-butadiene rubber, fluororubber, and various copolymers thereof.
[0070] Generally, the binder may be contained in an amount of 1 wt % to 20 wt %, preferably 1 wt % to 15 wt %, and more preferably 1 wt % to 10 wt %, based on the total weight of solids in the negative electrode slurry excluding the solvent.
[0071] The conductive material is a component for further improving the conductivity of the negative electrode active material. Such a conductive material is not particularly limited as long as it does not cause a chemical change in the battery and has conductivity, and may be, for example, graphite such as natural graphite or artificial graphite; carbon black such as acetylene black, ketjen black, channel black, furnace black, lamp black, or thermal black; conductive fiber such as carbon fiber or metal fiber; metal powder such as carbon fluoride, aluminum, or nickel powder; conductive whisker such as zinc oxide or potassium titanate; conductive metal oxide such as titanium oxide; or conductive material such as polyphenylene derivative.
[0072] The conductive material may be contained in an amount of 1 wt % to 20 wt %, preferably 1 wt % to 15 wt %, and more preferably 1 wt % to 10 wt %, based on the total weight of solids in the negative electrode slurry excluding the solvent.
[0073] The solvent may include water or an organic solvent such as NMP (N-methyl-2-pyrrolidone), and may be used in an amount that provides a preferred viscosity when the negative electrode active material, and optionally a binder and a conductive material, etc. are included. For example, the solvent may be included so that the concentration of the solid content including the negative electrode active material, and optionally a binder and a conductive material, is 50% by weight to 95% by weight, and preferably 70% by weight to 90% by weight.
[0074] When a metal is used as the negative electrode, the negative electrode may be manufactured by physically bonding, rolling, or depositing a metal thin film or a metal on the negative electrode current collector. The deposition method may be an electrical deposition method or a chemical vapor deposition method.
[0075] For example, the metal thin film itself or the metal bonded / rolled / deposited onto the negative electrode current collector may include one metal or an alloy of two metals selected from the group consisting of lithium (Li), nickel (Ni), tin (Sn), copper (Cu), and indium (In).
[0076] (3) Solid electrolyte layer The solid electrolyte layer may further contain a binder in addition to the solid electrolyte according to the present invention.
[0077] The binder is a component that aids in bonding between the conductive material, the active material, and the current collector. Examples of such binders include polyvinylidene fluoride, polyvinyl alcohol, carboxymethyl cellulose, starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene monomer, sulfonated ethylene-propylene-diene monomer, styrene-butadiene rubber, fluororubber, and various copolymers thereof.
[0078] Typically, the binder may be included in an amount of 1 wt % to 20 wt %, preferably 1 wt % to 15 wt %, and more preferably 1 wt % to 10 wt %, based on the total weight of the solid electrolyte layer.
[0079] The present invention provides a battery module including the all-solid-state battery as a unit cell, and a battery pack including the same. The battery module and the battery pack include the secondary battery having high capacity, high rate characteristics, and high cycle characteristics, and therefore can be used as a power source for medium- to large-sized devices selected from the group consisting of electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, and power storage systems. EXAMPLES
[0080] Below, preferred examples are presented to aid in understanding the present invention. However, the following examples are merely illustrative of the present description, and it will be apparent to those skilled in the art that various changes and modifications are possible within the scope and technical spirit of the present description. It goes without saying that such changes and modifications fall within the scope of the appended claims.
[0081] Manufacturing Example Three precursors, Li2S, P2S5, and LiCl, were dry mixed (ball milled) in a molar ratio of 5:1:2. During dry mixing, a planetary ball mill with zirconia balls was used and rotated at a speed of 300 rpm or more to ensure uniform mixing. The resulting mixed precursor was then heat-treated at 600°C for 12 hours to crystallize it, and was then pulverized again by ball milling to produce Li6PS5Cl with a sulphogermanite crystal structure. All of the above processes were carried out under an inert Ar atmosphere.
[0082] Examples and Comparative Examples Example 1 In 187 parts by weight of water, 95 parts by weight of cyclohexyl methacrylate (TCI), 5 parts by weight of α-butyl-ω-(3-methacryloxypropyl)polydimethylsiloxane (JNC, Silaplane FM-0721) (Mw: 5,000 g / mol), and 0.6 parts by weight of n-dodecyl mercaptan as a chain transfer agent were dispersed and mixed with a stirrer, followed by suspension polymerization at 75°C for 3 hours to produce Copolymer A (Mw: 45,000 g / mol, contact angle with water at 25°C: 107°). 5 parts by weight of the copolymer A was dissolved in 100 parts by weight of xylene to prepare a polymer composition.
[0083] The polymer composition and Li6PS5Cl having a silicogermanite crystal structure were mixed in a weight ratio of 1:1, stirred for 1 hour using a stirrer, and then the solvent was removed by vacuum drying to form a polymer coating layer on the Li6PS5Cl particles having a silicogermanite crystal structure.
[0084] As a result, a composite solid electrolyte was obtained in which a polymer coating layer containing a polymer having a weight-average molecular weight (Mw) of 45,000 g / mol and a contact angle with water of 107° at 25°C was formed on Li6PS5Cl particles having a silver germanite crystal structure.
[0085] Example 2 In 187 parts by weight of water, 95 parts by weight of cyclohexyl methacrylate (TCI), 5 parts by weight of α-butyl-ω-(3-methacryloxypropyl)polydimethylsiloxane (JNC, Silaplane FM-0721) (Mw: 5,000 g / mol), and 3.7 parts by weight of n-dodecyl mercaptan as a chain transfer agent were dispersed and mixed with a stirrer, followed by suspension polymerization at 75°C for 3 hours to produce Copolymer B (Mw: 13,000 g / mol, contact angle with water at 25°C: 108°).
[0086] A polymer composition was prepared in the same manner as in Example 1, except that the copolymer B was used instead of the copolymer A, and a polymer coating layer was formed on Li6PS5Cl particles having a silver germanite crystal structure.
[0087] As a result, a composite solid electrolyte was obtained in which a polymer coating layer containing a polymer having a weight-average molecular weight (Mw) of 13,000 g / mol and a contact angle with water of 108° at 25°C was formed on Li6PS5Cl particles having a silver germanite crystal structure.
[0088] Example 3 In 187 parts by weight of water, 95 parts by weight of cyclohexyl methacrylate (TCI), 5 parts by weight of α-butyl-ω-(3-methacryloxypropyl)polydimethylsiloxane (JNC, Silaplane FM-0721) (Mw: 5,000 g / mol), and 0.3 parts by weight of n-dodecyl mercaptan as a chain transfer agent were dispersed and mixed with a stirrer, followed by suspension polymerization at 75°C for 3 hours to produce Copolymer C (Mw: 86,000 g / mol, contact angle with water at 25°C: 107°).
[0089] A polymer composition was prepared in the same manner as in Example 1, except that the copolymer C was used instead of the copolymer A, and a polymer coating layer was formed on Li6PS5Cl particles having a silver germanite crystal structure.
[0090] As a result, a composite solid electrolyte was obtained in which a polymer coating layer containing a polymer having a weight-average molecular weight (Mw) of 86,000 g / mol and a contact angle with water of 107° at 25°C was formed on Li6PS5Cl particles having a silver germanite crystal structure.
[0091] Comparative Example 1 The Li6PS5Cl having a argonium sulfate-type crystal structure produced in Production Example was used as the solid electrolyte of Comparative Example 1.
[0092] Comparative Example 2 100 parts by weight of cyclohexyl methacrylate (TCI) and 0.6 parts by weight of n-dodecyl mercaptan as a chain transfer agent were dispersed in 187 parts by weight of water, and suspension polymerization was carried out at 75°C for 3 hours while mixing with a stirrer to produce polymer D (Mw: 45,000 g / mol, contact angle with water at 25°C: 89°).
[0093] A polymer composition was prepared in the same manner as in Example 1, except that the polymer D was used instead of the copolymer A, and a polymer coating layer was formed on Li6PS5Cl particles having a silver germanite crystal structure.
[0094] As a result, a composite solid electrolyte was obtained in which a polymer coating layer containing a polymer having a weight-average molecular weight (Mw) of 45,000 g / mol and a contact angle with water of 89° at 25°C was formed on Li6PS5Cl particles having a silver germanite crystal structure.
[0095] Comparative Example 3 In 187 parts by weight of water, 95 parts by weight of cyclohexyl methacrylate (TCI), 5 parts by weight of α-butyl-ω-(3-methacryloxypropyl)polydimethylsiloxane (JNC, Silaplane FM-0721) (Mw: 5,000 g / mol), and 0.05 parts by weight of n-dodecyl mercaptan as a chain transfer agent were dispersed and mixed with a stirrer, followed by suspension polymerization at 75°C for 3 hours to produce Copolymer E (Mw: 310,000 g / mol, contact angle with water at 25°C: 107°).
[0096] A polymer composition was prepared in the same manner as in Example 1, except that the copolymer E was used instead of the copolymer A, and a polymer coating layer was formed on Li6PS5Cl particles having a silver germanite crystal structure.
[0097] As a result, a composite solid electrolyte was obtained in which a polymer coating layer containing a polymer having a weight-average molecular weight (Mw) of 310,000 g / mol and a contact angle with water of 107° at 25°C was formed on Li6PS5Cl particles having a silver germanite crystal structure.
[0098] Comparative Example 4 In 187 parts by weight of water, 95 parts by weight of cyclohexyl methacrylate (TCI), 5 parts by weight of α-butyl-ω-(3-methacryloxypropyl)polydimethylsiloxane (JNC, Silaplane FM-0721) (Mw: 5,000 g / mol), and 10 parts by weight of n-dodecyl mercaptan as a chain transfer agent were dispersed and mixed with a stirrer, followed by suspension polymerization at 75°C for 3 hours to produce Copolymer F (Mw: 4,500 g / mol, contact angle with water at 25°C: 97°). For reference, the polymerization stability of α-butyl-ω-(3-methacryloxypropyl)polydimethylsiloxane decreased during the polymerization of copolymer F, and NMR analysis confirmed that 4.4 parts by weight of unreacted α-butyl-ω-(3-methacryloxypropyl)polydimethylsiloxane (88% by weight based on the content of the α-butyl-ω-(3-methacryloxypropyl)polydimethylsiloxane initially added) was detected.
[0099] A polymer composition was prepared in the same manner as in Example 1, except that the copolymer F was used instead of the copolymer A, and a polymer coating layer was formed on Li6PS5Cl particles having a silver germanite crystal structure.
[0100] As a result, a composite solid electrolyte was obtained in which a polymer coating layer containing a polymer having a weight-average molecular weight (Mw) of 4,500 g / mol and a contact angle with water of 97° at 25°C was formed on Li6PS5Cl particles having a silver germanite crystal structure.
[0101] Comparative Example 5 100 parts by weight of methyl methacrylate (Junsei Chemical Co., Ltd.) and 0.6 parts by weight of n-dodecyl mercaptan as a chain transfer agent were dispersed in 187 parts by weight of water, and the mixture was mixed with a stirrer and subjected to suspension polymerization at 75°C for 3 hours to produce Copolymer G (Mw: 44,000 g / mol, contact angle with water at 25°C: 69°).
[0102] A polymer composition was prepared in the same manner as in Example 1, except that the copolymer G was used instead of the copolymer A, and a polymer coating layer was formed on Li6PS5Cl particles having a silver germanite crystal structure.
[0103] As a result, a composite solid electrolyte was obtained in which a polymer coating layer containing a polymer having a weight-average molecular weight (Mw) of 44,000 g / mol and a contact angle with water of 69° at 25°C was formed on Li6PS5Cl particles having a silver germanite crystal structure.
[0104] [Table 1]
[0105] Experimental Example 1: Evaluation of ionic conductivity 150 mg of each of the composite solid electrolytes of Examples 1 to 3, the solid electrolyte of Comparative Example 1, and the composite solid electrolyte powders of Comparative Examples 2 to 5 were taken and placed in a SUS mold with a diameter of 13 mm. The mold was attached to a press machine together with insulating PEEK, and a potentiostat was connected to the SUS mold. After applying pressure of 370 MPa to sufficiently densify the electrolyte structure, the pressure was gradually reduced to maintain it at 100 MPa, and AC impedance measurements were performed at measurement frequencies of 1 Hz to 7 MHz. The ionic conductivity was calculated from the measured resistance value using a Nyquist plot, and is shown in Table 2 below. All measurements were performed in a dry room at a temperature of 22°C and a relative humidity of 0.7%.
[0106] Experimental Example 2: Evaluation of the amount of hydrogen sulfide gas generated 5 mg of each of the composite solid electrolytes of Examples 1 to 3, the solid electrolyte of Comparative Example 1, and the composite solid electrolyte powders of Comparative Examples 2 to 5 were taken and left for at least one hour in a glove box equipped with a hydrogen sulfide sensor (a drying air atmosphere controlled at a temperature of 25°C and a relative humidity of 0.59%). The rate of hydrogen sulfide generation per gram of composite solid electrolyte was calculated from the amount of hydrogen sulfide generated one hour after the sample was left standing. The rate of hydrogen sulfide generation is shown in Table 2 below.
[0107] [Table 2]
[0108] It can be confirmed that the composite solid electrolytes of Examples 1 to 3 have ionic conductivity suitable for use as an electrolyte, and generate hydrogen sulfide, a toxic gas, at a significantly slow rate.
[0109] In contrast, the composite solid electrolytes of Comparative Examples 2 and 5 have low hydrophobicity with contact angles of 89° and 69°, respectively, and thus it can be seen that the moisture blocking effect is reduced. And, it can be seen that the composite solid electrolyte of Comparative Example 3 has a high molecular weight of polymer, and the coating layer is thick and unevenly formed, resulting in low ion conductivity and reduced moisture blocking effect. Finally, it can be seen that the composite solid electrolyte of Comparative Example 4 has an insufficient moisture blocking effect because the molecular weight of the polymer is too low, resulting in reduced polymerization stability during the manufacturing process and a high amount of residual monomer that does not participate in the polymer polymerization reaction.
[0110] As a result, it is found that the composite solid electrolyte according to the present invention has a polymer coating layer on sulfide-based solid electrolyte particles, the polymer coating layer including a polymer (a copolymer of a hydrophobic acrylate monomer (containing an F element or an Si element, or containing a hydrocarbon having 10 or more carbon atoms) and an acrylate monomer (containing a hydrocarbon having 9 or less carbon atoms) forming the backbone of the polymer) having a weight average molecular weight (Mw) of 5,000 g / mol to 300,000 g / mol and a contact angle with water of 100° or more at 25° C., and has ionic conductivity suitable for use as an electrolyte and can prevent the sulfide-based solid electrolyte particles from decomposing and deteriorating.
Claims
1. Sulfide-based solid electrolyte particles; a polymer coating layer formed on the sulfide-based solid electrolyte particles; Including, The polymer coating layer includes a polymer having a weight average molecular weight (Mw) of 5,000 g / mol to 300,000 g / mol and a contact angle with water of 100° or more at 25° C., The polymer of the polymer coating layer is a copolymer of a hydrophobic acrylate monomer and an acrylate monomer forming a polymer backbone, The hydrophobic acrylate monomer contains an F element or an Si element, or contains a hydrocarbon having 10 or more carbon atoms, A composite solid electrolyte, wherein the acrylate monomer forming the polymer skeleton contains a hydrocarbon having 9 or less carbon atoms.
2. 2. The composite solid electrolyte of claim 1, wherein the sulfide-based solid electrolyte has a silver germanite crystal structure.
3. 2. The composite solid electrolyte according to claim 1, wherein the hydrophobic acrylate monomer is at least one selected from the group consisting of polydimethylsiloxane-based (meth)acrylate, N-octadecyl (meth)acrylate, stearyl (meth)acrylate, and perfluorohexylethyl (meth)acrylate.
4. 2. The composite solid electrolyte according to claim 1, wherein the acrylate monomer forming the polymer backbone is at least one selected from the group consisting of cyclohexyl (meth)acrylate, methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, iso-propyl (meth)acrylate, n-butyl (meth)acrylate, iso-butyl (meth)acrylate, tert-butyl (meth)acrylate, n-pentyl (meth)acrylate, and iso-pentyl (meth)acrylate.
5. The composite solid electrolyte of claim 1 , wherein the polymer of the polymer coating layer comprises a repeating unit represented by the following Chemical Formula 1 and a repeating unit represented by the following Chemical Formula 2: 【Chemistry 1】 In the above Chemical Formula 1, R 1 is hydrogen; or C 1 -C 10 is an alkyl group of the formula R 2 C containing cyclic hydrocarbons 4 -C 10 is an alkyl group of the formula 【Chemistry 2】 In the above Chemical Formula 2, R 3 ~R 8 are each independently hydrogen; or C 1 -C 10 is an alkyl group of the formula R 9 is a direct bond; 1 -C 10 an alkylene group of C 2 -C 10 an alkenylene group represented by the formula C 1 -C 10 an oxyalkylene group represented by the formula C 6 -C 30 an arylene group of the formula: 6 -C 30 is an oxyarylene group of the formula n is an integer of 1 or more.
6. The composite solid electrolyte of claim 1 , wherein the polymer coating layer is included in an amount of 0.1 to 10 parts by weight based on 100 parts by weight of the sulfide-based solid electrolyte particles.
7. 2. The composite solid electrolyte according to claim 1, having an ionic conductivity of 0.001 mS / cm or more.
8. When the composite solid electrolyte was exposed to an inert atmosphere at a temperature of 25° C. and a relative humidity of 0.5% to 0.6%, the hydrogen sulfide (H 2 S) is generated at a rate of 10 cm per 1 g of the composite solid electrolyte. 3 / h or less.
9. An all-solid-state battery comprising the composite solid electrolyte according to any one of claims 1 to 8.
Citation Information
Patent Citations
Preparation method of all-solid-state sulfide electrolyte for lithium ion battery
CN112421119A
Novel (meth)acrylate polymer compound and method for producing the same
JP1993295031A
Coated solid electrolyte for lithium battery, and all-solid secondary battery using the same
JP2010033732A
Protective sacrificial coating to enhance stability of battery materials
US20200395630A1
Coated particles, positive electrode, negative electrode, all-solid-state battery, and coating composition for sulfide-based all-solid-state batteries
WO2020095996A1